EDUKASI GIZI SEIMBANG PADA LANJUT USIA DALAM MENGHADAPI PANDEMI COVID-19 - Mitra Mitra; Nurlisis Nurlisis; Novita Rany; Ervira Dwiaprini As Syifa (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
The elderly is a group that is vulnerable to nutritional and health problems, especially problems related to degenerative diseases. Currently, Indonesia and the whole world are experiencing a corona virus pandemic or covid_19. The elderly are the group most at risk for contracting COVID_19. The purpose of community service is to increase the knowledge of the elderly about balanced nutrition in the face of the Covid 19 pandemic. The method of community service in the form of education and counseling uses WhatsApp (WA) media for the elderly or elderly families. The target group is the elderly or elderly families who are in the Working Area of ​​the Sapta Taruna Health Center Pekanbaru City. Telephone number/WA data for elderly or elderly families is needed to contact the elderly to participate as participants in educational and counseling activities. The material provided is balanced nutrition to increase body resistance in the face of the COVID-19 pandemic. Community service activities in the form of delivering material, health checks (blood pressure, measurement of height, weight and abdominal circumference) through meetings with the elderly then followed by education through Whatapps Group. The results of the pretest and posttest showed an increase in the knowledge of the elderly about balanced nutrition. This activity is expected to be a programmed and scheduled activity between the Health Centre and educational institutions and the next stage should be holding a meeting again with the health protocol by involving the elderly's family, so that the family can pass on information and education to the elderly.